Work Helper: mobile application based on probabilistic model for assessing the risk of occupational low back pain - Santos, José Welton dos; Santos, José Wendel dos; Santos, Pedro Vieira Souza; Carvalho, Glauco Luiz Rezende de (Brazilian Journal of Production Engineering, 2025)
The prevalence of musculoskeletal disorders, particularly occupational low back pain, represents a persistent challenge to public health and industrial productivity. This study aimed to develop a mobile application based on a probabilistic model for assessing the risk of occupational low back pain. Development followed the agile Scrum methodology, applying principles of service-oriented software engineering, with iterative cycles of implementation and testing on both the frontend and backend. To calculate the risk of low back pain, the probabilistic model proposed by Santos and Monteiro (2020), derived from multiple logistic regression with 84 workers, was adopted. During the implementation phase, the application, called Work Helper, demonstrated the ability to calculate ergonomic risk levels and generate personalized action plans for mitigation. The information is presented in interactive reports, including risk distribution by sector, key identified factors, and prioritized recommendations, providing immediate support for decision-making and continuous monitoring of occupational health. This performance demonstrates the feasibility of integrating probabilistic models into a mobile application, offering a replicable approach that contributes to the prevention of occupational low back pain in various work environments.
Keywords: Low back pain; Ergonomics; Mobile application